2013
DOI: 10.1038/bjc.2013.89
|View full text |Cite
|
Sign up to set email alerts
|

Does referral to specialist paediatric palliative care services reduce hospital admissions in oncology patients at the end of life?

Abstract: Background:Despite advances in the treatment of childhood cancer, some children continue to die from their disease. This study aimed to assess the impact of specialist paediatric palliative care services (SPPCSs) on the number of hospital admissions in children who subsequently died from cancer in Yorkshire, UK.Methods:An extract of patients aged 0–19 years from the Yorkshire Specialist Register of Cancer in Children and Young People (YSRCCYP) diagnosed from 1990 to 2009 were linked to inpatient hospital episo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 14 publications
0
46
0
6
Order By: Relevance
“…We excluded a further 3656 after screening the titles and abstracts, and retrieved 109 papers for full-text review (κ value = 0.25, 95% confidence interval [CI] 0.22-0.28, indicating fair agreement according to Fleiss 9 ). Nine articles fulfilled the inclusion criteria (Figure 1), 5,[10][11][12][13][14][15][16][17] (κ = 0.83, 95% CI 0.64-1.00, indicating almost perfect agreement). Two additional studies 18,19 were identified in the weekly automated search updates, for a total of 11 included studies.…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations
“…We excluded a further 3656 after screening the titles and abstracts, and retrieved 109 papers for full-text review (κ value = 0.25, 95% confidence interval [CI] 0.22-0.28, indicating fair agreement according to Fleiss 9 ). Nine articles fulfilled the inclusion criteria (Figure 1), 5,[10][11][12][13][14][15][16][17] (κ = 0.83, 95% CI 0.64-1.00, indicating almost perfect agreement). Two additional studies 18,19 were identified in the weekly automated search updates, for a total of 11 included studies.…”
Section: Study Selectionmentioning
confidence: 99%
“…Four cohort comparisons 11,12,14,15 used administrative data and survey techniques 14 to explore differences between cohorts of children with and without access to PPCPs. Observation periods varied, from the last day of admission before death to the referral to a PPCP.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nesse sentido, a hospitalização é configurada como uma experiência perturbadora, já que distancia a criança da vida cotidiana, de seus hábitos de descanso, lazer, higiene e alimentação, amigos e família. Isso pode fazer com que rejeite tudo que o ambiente hospitalar oferece (16).…”
Section: Discussionunclassified